Clinicopathological spectrum of central nervous system germ cell tumors: A single-institution retrospective study - Sreelekha Appasani; Neelima Radhakrishnan; Anitha Mathews (Indian Journal of Pathology and Microbiology)
Context: Central nervous system germ cell tumors (CNSGCTs) though rare is the second most common extragonadal site for GCTs. Aims: To determine the clinicopathological features of CNSGCTs diagnosed at our center. Settings and Design: A retrospective study of all histologically diagnosed CNSGCTs, during 2006-2019. Materials and Methods: The patients’ data were retrieved from the hospital information systems and analyzed. Statistical Analysis: Data on categorical variables were analyzed as percentages, and data on continuous variables calculated as mean. Chi-square test or Fisher’s exact test was used to study association between variables. Results: Of the total 34 cases with CNSGCT, age ranged from 1 to 27 years, majority in the second decade (19/34; 56%). Male: female (M: F) ratio was 1.6:1. Single site involvement was seen in 27 cases (27/34; 79%), whereas seven (7/34; 21%) showed bi/multifocal involvement. Among the unifocal cases, common sites involved were suprasellar (12/27; 44.4%), closely followed by the pineal (10/27; 37%). All multifocal tumors affected suprasellar compartment, being bifocal with pineal in four cases. A male gender predilection was noted among pineal region (9/10;90%) and multifocal tumors (5/7;71%). Germinoma was the commonest subtype (21/34; 61.8%) with male gender predilection (17/21; 81%) (M: F =4.3:1), with female predilection seen among mixed GCTs (MGCTs) (8/10; 80%) (M: F =1:4) and suprasellar location (M: F =1:2). Serum tumor markers (25 cases) and CSF markers (7 cases) were concordant with histology in all, except two cases. Conclusion: Though histology and immunohistochemistry were diagnostic, correlation between serum and/or CSF marker was essential to rule out GCT component(s) that may be missed on biopsy due to sampling error.